The twilight of neoliberalism in the USA? - Trevor Evans (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
The US economic expansion which began in 2009 was unusually prolonged but relatively weak. Profitability and investment strengthened between 2010 and 2015 but then began to falter. After Trump took office in 2017 there was a minor recovery in investment but the proceeds of major tax cuts were overwhelmingly used to finance pay outs to share owners. Unemployment fell steadily from 2010 but with a shift towards lower paid jobs. Median wages increased from around 2014, but while those for women had risen steadily since the 1980s, those for men only recuperated their 1980 level in 2018. By contrast, top incomes soared. The impact of the Covid19 epidemic was partly cushioned by huge government spending programmes, but unemployment among less skilled workers increased strongly, while the massive monetary response led to an unprecedented bonanza for the rich. The Biden government's first major initiative extended unemployment benefits and promoted a national response to the health emergency, but failed to secure an increase in the national minimum wage to 15 an hour.
Keywords: E25; E32; E44; E58; E65; F44; G01; 330; US economy; profitability; investment; finance; employment; wages